COMPARISON ANALYSIS OF TAX INCOME OF CLAUSE 25 OF SMALL, MEDIUM, AND MICRO BUSINESS UPON GOVERNMENTAL REGULATION 23 ABOUT TURNOVER (A case study in Orlando Pizza Small, Medium, and Micro Business Surabaya) - Bayu Adi; Moh Afrizal Miradji (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Small, Medium, and Micro Business of Orlando Pizza Surabaya is food business that is built since 2013. This pizza is liked by many circles in Surabaya area and around it. Besides that, Orlando Pizza sells the products by online and offline. The lovers are generally from circles of lecturers, students, and Surabaya people generally by various kinds of toppings. Sometimes, Orlando Pizza Surabaya together with the sales, it achieves turnover around Rp 15,000,000 per month, so therefore, about the taxation entity, Orlando Pizza Surabaya wants to compare between using report of Income Tax 25 of Small, Medium, and Micro Business or using clause of Income Tax 23 i.e. 1% from turnover. Based on the case above, one that becomes measure/method according to Yaana (2018) she explained it becomes 0.5% from turnover, therefore, I as a researcher wants to use this research as comparison reference and it can be made as example by other Small, Medium, and Micro Businesses about comparison entity between using financial report entity and entity compared as follows. Keywords: Small, Medium, and Micro Business, Tax Income 31 E, Governmental Regulation 46 of Turnover, Tax Income 25 of Small, Medium, and Micro Business